Kecemasan Mempengaruhi Gejala Insomnia pada Mahasiswa Tingkat I Fakultas Kedokteran Universitas Islam Bandung - Farah Amalia Mustika; Raden Ganang Ibnusantosa; Mia Kusmiati (UNISBA Press, 2023)
Abstract. Anxiety is often experienced by students who have just entered the tertiary level. Anxiety can affect both the quantity and quality of a person's sleep or what is commonly known as insomnia. Insomnia is defined as dissatisfaction with the quantity or quality of sleep. Insomnia is the most common type of sleep disorder worldwide. In previous research, it was found that anxiety and insomnia were often found in medical students. The purpose of this study was to determine the relationship between anxiety levels and insomnia symptoms in first grade students of the Faculty of Medicine, Islamic University of Bandung. The method used in this study was observational analytics with a cross-sectional design. The sample selection in this study was non-probability sampling with consecutive sampling. The research instrument used the Hamilton Rating Scale for Anxiety (HRS-A) to assess the level of anxiety and the Insomnia Severity Index (ISI). Data collection was taken through primary data by interviewing 96 student respondents. Data analysis used Fisher's exact test with p value = 0.05. The results obtained showed that there was a relationship between anxiety levels and insomnia symptoms in first-grade students of the Faculty of Medicine, Bandung Islamic University with a p value = 0.009 (p = <0.05). This study shows that freshmen at the Faculty of Medicine are a population with a fairly high level of anxiety, so this affects their sleep patterns. Keywords: Anxiety, Insomnia, Medicine, New students Abstrak. Kecemasan sering kali dialami oleh mahasiswa yang baru memasuki jenjang perguruan tinggi. Kecemasan dapat mempengaruhi baik secara kuantitas maupun kualitas dari tidur seseorang atau yang biasa disebut dengan insomnia. Insomnia didefinisikan sebagai ketidakpuasan dengan kuantitas atau kualitas tidur. Insomnia merupakan jenis gangguan tidur yang paling sering dijumpai dari seluruh dunia. Pada penelitian sebelumnya didapatkan bahwa kecemasan dan insomnia sering kali ditemukan pada mahasiswa Fakultas Kedokteran. Tujuan penelitian ini adalah untuk mengetahui hubungan antara tingkat kecemasan dengan gejala insomnia pada mahasiswa tingkat 1 Fakultas Kedokteran Universitas Islam Bandung. Metode yang digunakan pada penelitian ini adalah observational analytics dengan design cross sectional, pemilihan sampel pada penelitian ini adalah non-probability sampling dengan jenis consecutive sampling. Instrumen penelitian menggunakan Hamilton Rating Scale for Anxiety (HRS-A) untuk menilai tingkat kecemasan dan Insomnia Severity Index (ISI). Pengumpulan data diambill melalui data primer dengan wawancara kepada responden sebanyak 96 mahasiswa. Analisis data menggunakan uji Fisher exact dengan p value = 0,05. Hasil yang didapatkan menunjukkan adanya hubungan antara tingkat kecemasan dengan gejala insomnia pada mahasiswa tingkat 1 Fakultas Kedokteran Universitas Islam Bandung dengan p value = 0,009 (p = < 0,05). Penelitian ini menunjukkan bahwa mahasiswa baru Fakultas Kedokteran merupakan populasi dengan tingkat kecemasan yang cukup tinggi, sehingga hal tersebut mempengaruhi pola tidur mereka. Kata Kunci: Insomnia, Kecemasan, Kedokteran, Mahasiswa baru